Post-Research in Educational Sciences: Ontological and Epistemological Insights - Garbauskaitė-Jakimovska, Justina (Acta Paedagogica Vilnensia, 2019)
[full article and abstract in Lithuanian; abstract in English] In the academic community, it is becoming more outspoken that the traditional tools for perceiving the world have become not sufficient. The existing research methods used by social scientists are not flexible enough – they are unnecessarily simplifying the world and the processes that are happening in it. In order to address this issue, scientists started to question the procedures that are followed in order to explain the everyday processes, activities of organizations and individuals, but would not reduce them to something that can be known by observing or surveying a few informants or a few hundred of respondents. Rebecca Coleman and Jessica Ringrose, in an introduction to a book edited by them that is titled Deleuze and Research Methodologies, note the “need for methodologies capable of attending to the social and cultural world as mobile, messy, creative, changing and openended, sensory and affective” (Ringrose, Coleman 2013, 1). This article is aiming to expand the scientific discourse on the topic of post-research methodology in Lithuania. The objectives of the article are the following: 1) To describe the main philosophical ideas and theories that are connected to postqualitative research methodology; 2) To relate the theories and empirical research practice; 3) To describe new concepts: rhizoanalysis, schizoanalysis; 4) To highlight the tensions that are appearing in conducting postqualitative research. The main aspects that the article is focused on are the changing attitude toward data, the importance of philosophy, language, research procedures and the presentation of results. This article is based on an analysis of literature. Analyzed are the works of research methodology experts Elisabeth St. Pierre, Lisa Mazzei, Jessica Ringrose and those others who follow the ideas of the poststructuralists Deleuze and Guattari and take the initiative in bringing new perspectives on research in educational sciences.